Differential effects of Sutherlandia frutescens subs. microphylla on cell numbers, morphology, gene and protein expression in a breast adenocarcinoma and a normal breast epithelial cell line - Joubert, Fourie (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2007.